Precise, flexible and affordable gene stacking for crop improvement. Issue 5 (3rd September 2017) - Chen, Weiqiang; Ow, David W.
ABSTRACT: The genetic engineering of plants offers a revolutionary advance for crop improvement, and the incorporation of transgenes into crop species can impart new traits that would otherwise be difficult to obtain through conventional breeding. Transgenes introduced into plants, however, can only be useful when bred out to field cultivars. As new traits are continually added to further improve transgenic cultivars, clustering new DNA near previously introduced transgenes keep from inflating the number of segregating units that breeders must assemble back into a breeding line. Here we discuss various options to introduce DNA site-specifically into an existing transgenic locus. As food security is becoming a pressing global issue, the old proverb resonates true to this day: "give a man a fish and you feed him for a day; teach a man to fish and you feed him for a lifetime." Hence, we describe a recombinase-mediate gene stacking system designed with freedom to operate, providing an affordable option for crop improvement by less developed countries where food security is most at risk.